1968
DOI: 10.2136/sssaj1968.03615995003200040022x
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Products of Applied Phosphate in Limed Soils

Abstract: A study was made of the solubility of phosphate in limed soils to which liberal amounts of superphosphate had been added over a long period of time but to which no phosphate had been applied for at least 5 years prior to sampling. The control limed soils to which no phosphate had been applied were also included for comparison. A 20‐g sample of soil was extracted with 200 ml of 0.01M CaCl2 for 108 hours and the concentration of phosphate and pH were determined in the clear supernatant solution after centrifugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1970
1970
2003
2003

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This is especially true when phosphate is being removed by plants and periodically added in the form of fertilizers and decaying plant residues. Such compounds as variscite, strengite, hydroxyapatite, and fluorapatite should be the stable end-products of phosphate reactions in soils, and in certain conditions crystalline minerals do form in soils (Lindsay andMoreno, 1960, Murrman andPeech, 1968). However, these minerals form slowly at normal soil phosphate concentrations and temperatures (Low and Black, 1950, Aslyng, 1954, Lindsay and Moreno, 1960, Larsen, 1967, Wilson, 1968.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true when phosphate is being removed by plants and periodically added in the form of fertilizers and decaying plant residues. Such compounds as variscite, strengite, hydroxyapatite, and fluorapatite should be the stable end-products of phosphate reactions in soils, and in certain conditions crystalline minerals do form in soils (Lindsay andMoreno, 1960, Murrman andPeech, 1968). However, these minerals form slowly at normal soil phosphate concentrations and temperatures (Low and Black, 1950, Aslyng, 1954, Lindsay and Moreno, 1960, Larsen, 1967, Wilson, 1968.…”
Section: Introductionmentioning
confidence: 99%
“…Octocalcium phosphate seemed to be a fairly stable form in this soil since it was the predominant form in the native soil and it did not convert to hydroxyapatite even after 96 days of soil incubation. Formation of apatite in calcareous soils ( 8,15) may, therefore, be an extremely slow process ( 10 ).…”
Section: A) Conversion Of Superphosphate To Less Soluble Ca-phosphatimentioning
confidence: 99%
“…In calcareous soils, the phosphatic fertilizers are generally converted to less soluble forms such as dicalcium phosphate ( 7,11 ), octocalcium phosphates ( 22 ), and apatite ( 8,15). In the presence of higher organic matter content in soils, the conversion of labile phosphate to Jess available compounds was comparatively slower, The solubility of phosphorus from these compounds was also high, Thus LARSEN (8) reported that organic matter reduced the formation of apatite by 10 per cent and increased appreciably 395 the dissolution of phosphorus from newly formed crystals of apatite.…”
mentioning
confidence: 99%
“…WATER-SOLUBLE phosphate added to soil quickly disappears from the liquid phase, but it is a matter of conjecture whether the mechanism of this reaction is predominantly adsorption on the surface of the soil particles or a true precipitation of sparingly soluble salts. In calcareous soils the salts most likely to be formed are dicalcium phosphate, octocalcium phosphate, hydroxyapatite, and fluorapatite (As yng, I 954; Clark and Peech, 1955;Lehr and Brown, 1958;Hagin and Hadas, 1962;Murrmann and Peech, 1968). When a dilute phosphate solution or finely divided, soluble phos hate is added to soil, no reaction product has yet been directly detecte!…”
Section: Introductionmentioning
confidence: 99%